Research trends in COVID-19 vaccine: a bibliometric analysis - Tauseef Ahmad; Manal Abdulaziz Murad; Mukhtiar Baig; Jin Hui (Human Vaccines & Immunotherapeutics, 2021)
Background: In the last two decades the world has experienced many outbreaks of infectious diseases including the coronavirus disease 2019 (COVID-19) pandemic. COVID-19 was first reported in China and spread to more than 200 countries and territories. At present, there are no available treatment and vaccines for COVID-19. This study aimed to evaluate the global research trends in COVID-19 vaccine. Methods: On January 12, 2020, a comprehensive search of documents on COVID-19 was conducted in the Web of Science Core Collection database. HistCiteTM and VOSviewer softwares are used for citations and visualization mapping. Results: A total of 916 documents authored by 4,392 authors and published in 376 journals were included in the final analysis. Majority of the retrieved documents consisted of articles (n = 372, 40.6%). The most prolific authors were Dhama K (n = 10, 1.1%) and Hotez PJ (n = 10, 1.1%). The most active institution was the University of Oxford (n = 24, 2.6%). The leading journal in COVID-19 vaccine was Human Vaccine & Immunotherapeutics (n = 43, 4.7%). The most frequently used keywords were COVID (n = 597, 65.2%), and vaccine (n = 521, 56.9%). Furthermore, visualization mapping shows that COVID-19 was the most co-occurrence author keyword. The United States of America (USA) was the most productive country, 352 (38.4%). Conclusions: This is the first bibliometric study that provides detailed information about published literature on the COVID-19 vaccine. Majority of the publications were published in developed countries. The findings may useful for researchers and policymakers.